A Study Of Students’ Ability In Writing Procedure Text Through Youtube Video For The Tenth Grade Students Of SMA Ekasakti Padang - Rospita; Widya Juli Astria; Lailatul Husna (Kilau Publishing, 2026)
The purpose of this research was to describe student’s skill in writing procedure text through YouTube video to tenth grade students at SMA Ekasakti Padang. This Research had to be done because students’ low level of skill in writing due to lack of vocabulary in organizing ideas and lack of language comprehension. This research is a descriptive qualitative research with population of 17 students at tenth grade Phase E. The technique of collecting data was total sampling technique and the instrument for this research was writing procedure text test after they watch a Youtube video titled ‘How to Use A Camera’. The results showed that student’s writing skill was fair to low because based on five scoring aspect in writing (content, organization, vocabulary, language feature, and mechanic), the majority of students was in fair and low category. This result showed that even though Youtube video helped students to understand he structure and the steps in procedure text, students still have difficulties in grammar, vocabulary, and spelling. Therefore, guided integration of Youtube video with writing exercise and vocabulary development is highly recommended.